Explaining barriers to the usage of learning object repositories : comparison between Europe and Latin America - Liao, Laidis Loriel (2020)
Learning Object Repositories have a great potential to enhance knowledge sharing in the teaching community. However, the usage of Learning Object Repositories has not met the expectations that the supporting institutions (universities, colleges and organizations) had regarding its success. The barriers to the usage of LORs were explored to understand what stops users from being actively involved in creating, reusing and sharing contents on LORs. The investigation aimed to find out what barriers do managers consider the most significant to the use of LORs, how do barriers to LOR usage in Eu-rope compare to those in Latin America and what are the main approaches that have been implemented to overcome the identified barriers. A qualitative approach was taken for obtaining an in-depth understanding of these topics. Barriers to knowledge sharing found in literature were mapped to the con-crete LOR scenario and a questionnaire was created for conducting interviews to twenty LOR managers from both Europe and Latin America. The answers from the informants were analyzed to understand the relevance of each barri-er, as well as the differences between these barriers as perceived by managers in Europe vs managers in Latin America. As expected, human-centered issues affect the usage of LOR. For instance, the main barriers affecting LOR usage found for Europe are language differences, knowledge sharing issues and lack of time. On the other hand, for Latin America the main barriers found are lack of skills, lack of sufficient infrastructure and lack of time, a finding that also shows how Latin America struggles with the “Global South” problems. The findings also reflect the relevance of the digital divide as an impediment to knowledge sharing and how most of the studied barriers could be overcome with the creation of policies to support LOR usage and exploit all the benefits it could bring to the teaching community.